A comparative analysis of three Sunni Muslim organizations on 'moderate' and 'radical' Islam in Egypt, Morocco and Indonesia. Issue 2 (3rd April 2021) - Pektas, Serafettin
ABSTRACT: The distinction between 'moderate' and 'radical' Islam has played a key role in tackling contemporary militant religious extremism. This article examines three prominent Sunni Muslim institutions that uphold this distinction and present themselves as the peaceful and moderate voices of 'true Islam', namely al-Azhar al-Sharīf of Egypt, Nahdlatul Ulama of Indonesia and al-Rabita al-Muhammadiyya lil-'Ulama' of Morocco. The article provides a critical, comparative analysis of their religious discourses and theological strategies in developing an 'exceptional' and 'moderate' Sunni response to jihadist militancy, particularly after the emergence of the so-called 'Islamic State' in Syria and Iraq (IS). It demonstrates that each institution has developed its own brand of moderateness with different motivations, argumentations, content and religious justifications. As such, this article challenges the moderate-versus-radical dichotomy by revealing that there are multiple discourses on moderation, instead of it being one single and coherent moderate bloc.